Optical goniometer device for continuous monitoring of the knee movement in physiotherapy application - Ghassan, Maan Salim (2022)
Knee joint is the most crucial among the lower limbs joints due to its exposed location and its major role which carries the entire burden of the body practically our entire life. Hence, by being able to measure the knee joint angle accurately during continuous movement, allows the physiotherapist to detect knee joint damage at early stages before it turns into an injury or permanent scar tissue. Due to the limited number of continuous monitoring devices applicable for diagnosis and treatment stage of the knee, most physicians opted for X-ray and magnetic resonance imaging (MRI) technologies to have some insight on the knee issue before suitable treatment can be recommended. Aside from being expensive for general use of MRI, X-ray on the other hand can cause short-term side effects due to radiation exposure. Knee joint angle measurement devices technologies include but are not limited to the implementation of accelerometer, electrogoniometer, torsiometer, acoustic, visual sensory, and optic fibre. There are many limitations to these technologies that require improvements before they can become clinically applicable such as accuracy issues, limited range of motion measurement, and inability to monitor continuous movement measurement of the knee joint, which have been discussed thoroughly in this research. The need for technologies with higher accuracy, reliability, able to measure the full knee range of motion, applicable for continuous motion measurement and lower cost have always been a crucial factor. The use of optical based devices provides significant contribution in this area due to their advantages such as immunity to electromagnetic interference, lightweight and possibly small sensor setup. However, the application of intensity-based optical fibre sensor for human joint motion detection resulted in limited detection angle, where most sensor are not able to detect angle variation of more than 90ᵒ. To improve this limitation, an optical sensor approach with mechanical-assisted components assembly that translates angular movement to linear movement was developed. The light detection on the photodiode array sensor at different pixels is analysed to represent the angle movement of the knee. The sensor is securely attached to a medical standard knee brace tool to ensure firm sensor placement on the knee area. Based on current study, the proposed optical sensor has a range of motion between 0 to 160ᵒ, with 0.08ᵒ resolution, has a 210.5 sampling rate per second, which allows it to present and record a real time graphical output to demonstrate the knee joint activity performance. Moreover, the proposed device was able to give an excellent internal consistency obtained by Cronbach’s Alpha analysis of 0.967, and has 98.044% correlation with the gold standard goniometer.